Habitat use by fishes in coral reefs, seagrass beds and mangrove habitats in the Philippines. - Kentaro Honda; Yohei Nakamura; Masahiro Nakaoka; Wilfredo H Uy; Miguel D Fortes (PLoS ONE, 2013)
Understanding the interconnectivity of organisms among different habitats is a key requirement for generating effective management plans in coastal ecosystems, particularly when determining component habitat structures in marine protected areas. To elucidate the patterns of habitat use by fishes among coral, seagrass, and mangrove habitats, and between natural and transplanted mangroves, visual censuses were conducted semiannually at two sites in the Philippines during September and March 2010-2012. In total, 265 species and 15,930 individuals were recorded. Species richness and abundance of fishes were significantly higher in coral reefs (234 species, 12,306 individuals) than in seagrass (38 species, 1,198 individuals) and mangrove (47 species, 2,426 individuals) habitats. Similarity tests revealed a highly significant difference among the three habitats. Fishes exhibited two different strategies for habitat use, inhabiting either a single (85.6% of recorded species) or several habitats (14.4%). Some fish that utilized multiple habitats, such as Lutjanus monostigma and Parupeneus barberinus, showed possible ontogenetic habitat shifts from mangroves and/or seagrass habitats to coral reefs. Moreover, over 20% of commercial fish species used multiple habitats, highlighting the importance of including different habitat types within marine protected areas to achieve efficient and effective resource management. Neither species richness nor abundance of fishes significantly differed between natural and transplanted mangroves. In addition, 14 fish species were recorded in a 20-year-old transplanted mangrove area, and over 90% of these species used multiple habitats, further demonstrating the key role of transplanted mangroves as a reef fish habitat in this region.